The painted icons : wall paintings of the Sauras of South Orissa - Pathy, Dinanath; Crafts Council of Orissa (New Delhi : Harman Pub. House ; Bhubaneswar : Crafts Council of Orissa, 1996)
Study on behalf of the Crafts Council of Orissa.
Keywords: Icon painting -- India -- Odisha; Icons -- Cult -- India -- Odisha; Odisha (India) -- Religion; 20-90